The stiff total knee arthroplasty: causes, treatment modalities and results - Rodríguez-Merchán, E. Carlos (EFORT Open Rev, 2019)
It is clear that the stiff total knee arthroplasty (TKA) is a multifactorial entity associated with preoperative, intraoperative and postoperative factors. Management of the stiff TKA is best achieved by preventing its occurrence using strategies to control preoperative factors, avoid intraoperative technical errors and perform aggressive, painless postoperative physical medicine and rehabilitation; adequate pain control is paramount in non-invasive management. Careful attention to surgical exposure, restoring gap balance, minimizing surgical trauma to the patellar ligament/extensor mechanism, appropriate implant selection, pain control and adequate physical medicine and rehabilitation (physiotherapy, Astym therapy) all serve to reduce its incidence. For established stiff TKA, there are multiple treatment options available including mobilization under anaesthesia (MUA), arthroscopic arthrolysis, revision TKA, and combined procedures. Cite this article: EFORT Open Rev 2019;4:602-610. DOI: 10.1302/2058-5241.4.180105